Case Report: Paroxysmal hyperhidrosis as an initial symptom in a patient with anti-LGI1 encephalitis - Qiao, Tingting; Chen, Lanlan; Jiang, Li; Wei, Hua; Chen, Xin; Li, Xiaobo; Chen, Yingzhu; Xu, Yao (Frontiers in Immunology, 2022)
Anti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis is the second most common cause of autoimmune encephalitis and is characterized by cognitive impairment, psychiatric disorders, and faciobrachial dystonic seizures. In recent decades, literature reports have expanded the phenotypic spectrum associated with the LGI1 autoantibody. The present report describes the case of a 58-year-old man who presented with repetitive unilateral hyperhidrosis of the body and arm as an initial symptom and gradually developed psychiatric symptoms, involuntary movements of the face and arms, and progressive cognitive decline. Anti-LGI1 antibodies were positive in both the serum and cerebrospinal fluid at approximately 2 months after symptom onset, and the patient was, therefore, diagnosed with anti-LGI1 encephalitis. His symptoms, namely hyperhidrosis and involuntary movements, were not relieved by antiepileptic drug treatment, but responded favorably to high-dose steroid therapy and intravenous immunoglobulin. We interpreted the repetitive unilateral hyperhidrosis as possible epilepsy. Based on this case, unilateral hyperhidrosis of the body and arm as a rare neurological presentation can be added to the phenotypic spectrum of anti-LGI1 encephalitis, and early recognition of this manifestation might support timely diagnosis and treatment.